FMIS research: a reflection on IWMI's 25 years in Nepal - Pant, Dhruba (2010)
International Water Management Institute, the then International Irrigation Management Institute (IWMI) began its activities in Nepal since 1986 with a Memorandum of Understanding with His Majesty?s Government of Nepal, now the Government of Nepal. The primary objectives were to strengthen the research capability of Water and Energy Commission Secretariat, promote collaborative research in Farmer Managed Irrigation Systems (FMIS), Irrigation Management Transfer (IMT) and Agency Managed Irrigation Systems (AMIS). Pioneering researches in FMIS and AMIS were carried out in Nepal by IWMI and it laid impact on participatory irrigation management through understanding the role of water users association for effective management of irrigation system. The researches in Nepal was also important for its contribution to the water sector management in the developing country through the promotion of science based studies and action research. The main areas of contribution of IWMI research were in policy formulation, methodology development and Institutional Strengthening and Capacity Building for irrigation research. Therefore, this paper will try to look into the FMIS, AMIS and other researches that IWMI has undertaken, their importance for water management in Nepal and the lessons learnt is expected to be of interest to policy makers, planners, researchers and the scientific community.